ALCOHOL AND THE RISK OF NON-COMMUNICABLE DISEASE: CONTROL STRATEGIES IN THE RUSSIAN FEDERATION - G. Ya. Maslennikova; R. G. Oganov (Кардиоваскулярная терапия и профилактика)
Alcohol and the risk of non-communicable disease: control strategies in the Russian Federation.